Making world heritage truly global : the culture certificate scheme - Bruno S. Frey; Paolo Pamini (Center for Economic Studies and ifo Institute (CESifo), 2009)
Culture has attributes of a global public good that needs to be preserved for mankind as a whole. World Culture Certificates are proposed to efficiently preserve World Heritage. The community of nations has to agree on the Global Heritage List and how much each nation is to contribute to that purpose. Each World Heritage site conserved is acknowledged through the issuance of a tradable Certificate. Countries and private firms are induced to seek sites where financial resources can be spent most productively. This leads to an efficient allocation of resources to preserve World Heritage.
Keywords: Z11; D60; F50; H87; 330; global public good; World Heritage; Cultural Certificates; monuments; UNESCO; Kulturgut; Öffentliches Gut; Emissionsrechte; Welt